Superhydrophobic surface processing for metal 3D printed parts. (December 2022) - Huang, Wuji; Nelson, Benjamin; Tian, Steven; Ordikhani-Seyedlar, Ramin; Auyeung, Raymond C.Y.; Samanta, Avik; Hu, Hui; Shaw, Scott; Lamuta, Caterina; Ding, Hongtao
Highlights: Wettability of the as-printed metal parts is unstable. An increase of water contact angle is observed after exposure in air for a month. Chemical immersion treatment only produces rose petal effect. nHSN is able to generate lotus-like superhydrophobic surface. Laser texturing enhances the chemical reaction in the following chemical treatment and therefore increases superhydrophobicity. The difference of surface topography between the petal-like surfaces and lotus-like surfaces are quantified. Abstract: Surface engineering methods for wettability modification of 3D-printed metal parts have attracted considerable attention, in large part due to the applicability of these components in fluid-related fields. In this study, two processing methods have been developed to produce superhydrophobic surfaces on AlSi10Mg and Ti6Al4V fabricated using laser powder bed fusion (L-PBF). Surface chemistry and topography are investigated as two primary determinants of the resulting wettability state. On its own, chemical immersion treatment can impart the rose petal effect on these additively manufactured metal surfaces, viz. high water contact angle coupled with high water adhesion. When laser surface texturing is performed prior to chemical treatment, the lotus leaf effect is achieved instead, with the surface showing high water contact angles and low water adhesion. Surface chemistry analysis shows that a fluorosilane reagent reacts more favorably with laser textured surfaces, thus imparting greater hydrophobicity. Surface topography is also shown to play a significant role in the resulting wetting behavior. By applying surface topography parameters, Spc and r, the topographical distinction between surfaces displaying the rose petal effect and the lotus leaf effect is quantitatively described. Graphic abstract: Image, graphical abstract